Peran Customer Service (CS) Dalam Meningkatkan Loyalitas Nasabah Produk Tabungan Bank Sumut Cabang Syariah Sibolga - Yola Aprilia Sibagariang; Khairina Tambunan (Pusat Riset dan Inovasi Nasional, 2024)
In providing services, the role of customer service is directly related to consumer choices, so reliable customer service is needed. This research aims to explain the role of customer service in increasing customer loyalty. The research method uses qualitative methods with data collection techniques through interviews and literature studies. The results of this research show that the role of customer service in increasing customer loyalty is very important through the services provided by the customer service department. Customer service is in the form of providing convenience to customers, because customer service is a connecting bridge or intermediary for banks and customers who want to obtain available bank services or products. Customer loyalty can be determined by their desire to continue using the services of Bank Sumut Syariah Branch in Sibolga City, this can be shown by their satisfaction with the services provided so far. The creation of customer satisfaction shows the loyal attitude of customers towards Bank Sumut Syariah Branch in Sibolga City.